How Government Spending on Public Sector Affect The Economic Growth? - Ambya, Ambya (JEJAK: Jurnal Ekonomi dan Kebijakan, 2020)
Fiscal decentralization is an effort to reform governance so that it has a more effective and efficient structure so that it can improve services to the community. Efforts to achieve these goals are largely determined by the availability of human resources, natural resources, and other economic potential. The formation of New Autonomous Regions (NAR) grew rapidly, but on the other hand local governments were unable to fund development activities independently but were dependent on balance funds. The objective to be achieved is to analyze the effect of regional government spending on education, health, and infrastructure, as well as other variables namely labor on the economic growth of new autonomous regions in Indonesia. The analysis model used is panel data regression. The results of the study prove that local government spending in real per capita education, real health (lag-1) per capita, and real per capita infrastructure, and the number of workers have a positive and significant effect on economic growth. Economic growth that occurs in the district is not different from the city, so also in the base sector is mostly no different except the mining and quarrying sector.